Psychometric validation of the Aut-Eat Questionnaire (AEQ) in Turkish children with autism spectrum disorder: Associations with maternal quality of life and depression - Gunduz, Busra Nur Dambasan; Erus, Seher Merve; Orengul, Abdurrahman Cahid (ELSEVIER SCI LTD, 2026)
Objective: This study aimed (1) to examine the psychometric properties of the Aut-Eat Questionnaire (AEQ) in a clinical sample of children with autism spectrum disorder (ASD) in T & uuml;rkiye and (2) to investigate associations between children's eating problems, maternal quality of life (QoL), and maternal depression, including a mediation model. Methods: The sample comprised 352 children with ASD (2-12 years) and their mothers, recruited from a tertiary child psychiatry outpatient clinic. Mothers completed the AEQ, Brief Autism Mealtime Behavior Inventory (BAMBI), WHOQOL-BREF, and Hospital Anxiety and Depression Scale (HADS). A subsample of 18 mothers completed the AEQ again after 2-3 weeks. Internal consistency, short-interval test-retest reproducibility, and confirmatory factor analysis (CFA) were used to evaluate the AEQ. Convergent validity was examined via correlations with BAMBI scores and weight percentiles. Mediation analysis (PROCESS, Model 4) tested whether maternal depression mediates the association between maternal QoL and children's eating problems, controlling for child gender, maternal age, maternal education, and ASD severity. Results: The AEQ showed high internal consistency and excellent short-interval test-retest reproducibility. CFA supported the six-factor structure with acceptable fit indices. AEQ subscales correlated significantly with BAMBI scores, supporting convergent validity. Children's eating problems were positively associated with maternal anxiety and depression and negatively associated with maternal QoL. Maternal depression emerged as a partial statistical mediator of the association between maternal QoL and children's eating problems. Conclusion: The Turkish AEQ is a reliable and valid tool for assessing eating problems in children with ASD. Findings highlight the importance of maternal QoL and depression in understanding and treating feeding difficulties, underscoring the need for family-centered, caregiver-focused interventions in psychiatric settings.
Keywords: Autism spectrum disorder; Eating problems; Aut-Eat Questionnaire; Maternal quality of life; Maternal depression; Psychometric validation; BEHAVIOR INVENTORY; MEALTIME PROBLEMS; PARENTING STRESS; FEEDING PROBLEMS; MOTHERS; RELIABILITY; DISTURBANCES; SYMPTOMS; VALIDITY; Education & Educational Research; Psychology; Psychiatry; Rehabilitation